2007
DOI: 10.1111/j.1365-2044.2007.05182.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the TruView EVO2 laryngoscope

Abstract: SummaryThe TruView EVO2 laryngoscope was compared with the traditional Macintosh laryngoscope in 200 patients who required tracheal intubation for elective surgery. Mallampati score determined prior to laryngoscopy was significantly related to the view of the glottis during laryngoscopy for both laryngoscopes. The view of the larynx was better with the TruView EVO2 laryngoscope than with the Macintosh laryngoscope in patients with a Cormack and Lehane grade greater than 1 (p < 0.01). The mean time to intubate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 11 publications
7
47
0
1
Order By: Relevance
“…(2011) in their study found that the mean time to intubation was significantly shorter with the Macintosh laryngoscope than the Truview laryngoscope. 12,13,15 Thus, the result in our study was comparable to the above study. We experienced considerable difficulties in advancing the tracheal tube towards the view of the digital camera, a finding again previously reported by other investigators.…”
Section: Discussionsupporting
confidence: 90%
“…(2011) in their study found that the mean time to intubation was significantly shorter with the Macintosh laryngoscope than the Truview laryngoscope. 12,13,15 Thus, the result in our study was comparable to the above study. We experienced considerable difficulties in advancing the tracheal tube towards the view of the digital camera, a finding again previously reported by other investigators.…”
Section: Discussionsupporting
confidence: 90%
“…Truview EVO2 ® laryngoscopes have been reported to have advantages in patients with a low risk of difficult intubation when compared to the Macintosh-type laryngoscope (12,13), whereas, in some case reports, patients with difficult intubation with Macintosh laryngoscopes have been reported to have successful intubations with Truview EVO2 ® -type laryngoscopes (14,15).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that this device produces superior laryngeal views and requires less force during laryngoscopy compared with a Macintosh laryngoscope blade. 54,55 Like other rigid fiberoptic laryngoscopes, it is robust and easily portable and can control soft tissue well during laryngoscopy. However, these devices have not gained widespread use in clinical practice.…”
Section: Rigid Fiberoptic Laryngoscopesmentioning
confidence: 99%